DYNAMIC RELAXATION IN THE ITERATIVE METHODS FOR SOLVING NONLINEAR THREE-PHASE CIRCUITS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
The Hănțilă method has proven its effectiveness in solving non-linear three-phase circuits. It is the only effective method for analyzing non-linear three-phase circuits containing machines with different sequence reactances. Since solving a system of equations is unnecessary, the computational effort is reduced, and a large number of harmonics can be considered. The convergence of the method is certain - demonstrated mathematically and allows the use of overrelaxation. To develop the method, we analyze the efficiency of computing a dynamic overrelaxation factor for accelerating the computational algorithm.
Keywords: Nonlinear three-phase circuits; Picard-Banach iterative solution; Hănțilă method; Convergence acceleration; Dynamic overrelaxation